2022
DOI: 10.1016/j.mex.2021.101603
|View full text |Cite
|
Sign up to set email alerts
|

Hide-and-seek: Threshold values and contribution towards better understanding of recovery rate in microplastic research

Abstract: Microplastic pollution has become one of the most pressing environmental issues. A fundamental criterion for risk assessment is the concentration of found microplastic that can be altered during microplastic isolating from the sample. Recovery rate (i.e. positive control) is an important feedback component that identifies accuracy, quality and efficiency of sample processing, same as physical and chemical impact. Here, using 100 µm red polystyrene (PS) beads we have tested some methodological steps that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…It showed that MPPs with a density higher than water can be sampled from the middle of a water column of a technical and turbulent mixed stream. The recovery rate is higher than the average recovery rate reported by Dimante-Deimantovica et al [1] for an MP analysis protocol with seven transfer steps and comparable particle size (40%, 100 µm). The analysis protocol in this study had eight transfer steps.…”
Section: Pvc Recovery Ratecontrasting
confidence: 58%
See 1 more Smart Citation
“…It showed that MPPs with a density higher than water can be sampled from the middle of a water column of a technical and turbulent mixed stream. The recovery rate is higher than the average recovery rate reported by Dimante-Deimantovica et al [1] for an MP analysis protocol with seven transfer steps and comparable particle size (40%, 100 µm). The analysis protocol in this study had eight transfer steps.…”
Section: Pvc Recovery Ratecontrasting
confidence: 58%
“…While blanks are important to control sample contamination with ubiquitous MP and to ensure the MP concentration in a sample is not overestimated, recovery rates are important to quantify false-low results. In a review of several research papers, Dimante-Deimantovica [1] showed that the recovery rate of 100-µm microplastic particles (MPPs) ranges between 40 and 80%, decreasing with the number of transfer steps in sample preparation. Other studies show that the recovery rate decreases rapidly with the particle diameter [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Especially the single model approach seems to be acceptable, as recall and precision are around 90%. However, we decided to increase precision and recall by using the human-machine teaming approach for several reasons: In spectroscopic microplastic analysis, recovery rates are low [11,29]. Therefore, any possibility to increase accuracy should be taken.…”
Section: Practical Relevance Of the Resultsmentioning
confidence: 99%
“…the number of sample transfers during sample puri cation affects the recovery rate. Therefore, it can be assumed that the actual MP concentration in the lake sediments might be at least twice or even three times higher 43 . Air background samples and procedural/ eld blanks were analysed in parallel with lake sediment samples and were not considered to change the results signi cantly (see more details in the methods section).…”
Section: Discussionmentioning
confidence: 99%